(untitled) (Bangladesh Journal of Botany, 2023)
In the mountainous area of Yunnan-Guizhou Plateau, phosphorus and nitrogen are important factors that limit primary productivity and affect the distribution of plant communities. Alternation of wet and dry has a significant effect on the migration of various elements such as C, N, and P in soil. Taking the rhizosphere soil of the dominant plants in the phosphorus-rich mountainous area in the Dianchi Lake Basin as the research object. Six sets of different humidity treatment methods: blank constant humidity, blank dry and wet alternation, nitrogen constant humidity, nitrogen addition dry and wet alternation, carbon constant humidity, and carbon add dry and wet alternation were assessed. Responses of soluble total nitrogen and soluble total phosphorus to six treatments in plant root zone were investigated. The results showed that the contents of dissolved total nitrogen (DTN) and dissolved total phosphorus (DTP) in soil leachate and their changes of Erianthus rufipilus and Eupatorium adenophorum under different treatment conditions increased first and then decreased. In the carbon addition group, the DTN content of the soil leachate in the alternating dry and wet treatment was significantly higher than that in the constant humidity treatment, but there was no significant difference in the nitrogen addition group. The three factors of water treatment and sampling time have significant effects on the DTN content of soil leachate, and the interaction between the three also has a significant effect on it. Bangladesh J. Bot. 51(4): 855-862, 2022 (December) Special